Characterization and Rheological Study of a Tunisian Bentonite for its Use in the Drilling Fluids - M'bodj, Ousseynou; Ayadi, Mounir; Bennam, Memia; Kbir Ariguib, Najia; Trabelsi Ayadi, Malika (Asian Journal of Chemistry, 2010)
The Jebel Shemsi ore contains 81 % of clays; mainly quartz and carbonate are present as impurities. The dominant phase in the clay fraction is smectite (80%), it also contains illite (15%) and some kaolinite. The cationic exchange capacity (CEC) value of the purified clay is 87 meq/100 g of calcined clay; the total specific surface area (ST) is equal to 711 m2/g. The dehydration (hygroscopic water) of the raw and purified clay occurs around 109°C and its dehydroxylation at 502°C for the raw bentonite and at 468°C after purification. The study of the clay percentage (w/w) effect on the rheological properties shows that the flow curves have a Newtonian behaviour for the clay percentage lower than 10%. After this percentage, the behaviour becomes rheofluidifiant. The effect of pH on the rheological properties has been studied at the clay percentage of 10% and shows two states of maximum interaction in acidic medium (pH range 2-4) and basic medium (pH range 9.5-11). The suspensions corresponding to the first maximum are gels and exhibit a rheofluidifiant behaviour, whereas those corresponding to the second basic maximum are gels but flow easily and exhibit a Newtonian behaviour. The natural pH of the clay (pH = 7.2) corresponds to the minimum of interactions.